2020
DOI: 10.32630/sukowati.v3i2.153
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Teknologi Informasi Dan Komunikasi Terhadap Peningkatan Nilai Tambah Sektor Pariwisata Di Jawa Tengah

Abstract: Indonesia merupakan salah satu negara yang mengalami perkembangan Teknologi Informasi dan Komunikasi (TIK) yang pesat. Adanya perkembangan TIK yang pesat maka dapat mendorong sektor pariwisata, salah satunya di Provinsi Jawa Tengah. Namun, terdapat berbagai kabupaten atau kota yang memiliki hubungan negatif antara persentase pengguuna internet dengan nilai tambah sektor pariwisata. Penelitian ini bertujuan untuk memberikan gambaran kondisi sektor pariwisata dan persentase pengguna internet di Jawa Tengah dan m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…On the other hand, fulfilling food needs has also been carried out through digitalization efforts, such as those developed in Sleman District (E. T. Wibowo, 2020). Previous research conducted in Central Java Province also showed that the percentage of technology use, in general, can negatively and significantly affect the number of poor people (Dewi et al, 2023). The second component of pro-poor expenditures is health expenditure.…”
Section: Journal Of Internationalmentioning
confidence: 99%
“…On the other hand, fulfilling food needs has also been carried out through digitalization efforts, such as those developed in Sleman District (E. T. Wibowo, 2020). Previous research conducted in Central Java Province also showed that the percentage of technology use, in general, can negatively and significantly affect the number of poor people (Dewi et al, 2023). The second component of pro-poor expenditures is health expenditure.…”
Section: Journal Of Internationalmentioning
confidence: 99%
“…Ditandai dengan peningkatan 1% dari pengguna internet maka akan meningkatkan nilai tambah sektor pariwisata sebesar 1,59% di Provinsi Jawa Tengah (Dewi dan Wulansari, 2020). Pada fenomena perkembangan pariwisata dengan ICT penelitian ini akan melihat seperti apa Baturraden Adventure Forrest (BAF) menggunakan media internet untuk menjaring konsumennya dan bagaimana komunikasi yang antar BAF dan konsumennya.…”
Section: Pendahuluanunclassified